The bidirectional relationship between periodontal disease and pregnancy via the interaction of oral microorganisms, hormone and immune response - Wen, Xingyue; Fu, Xiangqing; Zhao, Chongjun; Yang, Lei; Huang, Ruijie (Frontiers in Microbiology, 2023)
Periodontal disease has been suggested to be linked to adverse pregnancy outcomes such as preterm birth, low birth weight, and preeclampsia. Adverse pregnancy outcomes are a significant public health issue with important clinical and societal repercussions. This article systematically reviews the available epidemiological studies involving the relationship between periodontal disease and adverse pregnancy outcomes over the past 15 years, and finds a weak but independent association between adverse pregnancy outcomes and periodontal disease. The bidirectional association and the potential mechanisms are then explored, focusing on three possible mechanisms: inflammatory reaction, oral microorganisms and immune response. Specifically, elevated systemic inflammation and increased periodontal pathogens with their toxic products, along with a relatively suppressed immune system may lead to the disruption of homeostasis within fetal-placental unit and thus induce adverse pregnancy outcomes. This review also explains the possible mechanisms around why women are more susceptible to periodontal disease. In conclusion, pregnant women are more likely to develop periodontal disease due to hormonal changes, and periodontal disease has also been suspected to increase the incidence of adverse pregnancy outcomes. Therefore, in order to lessen the risk of adverse pregnancy outcomes, both obstetricians and dentists should pay attention to the development of periodontal diseases among women during pregnancy.